PENERAPAN MODEL PEMBELAJARAN KANCING GEMERINCING UNTUK PEMERATAAN KEAKTIFAN SISWA KELAS IX MATA PELAJARAN IPS DI SMPN 11 MALANG - Septika Liaini Sari (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2020)
This study aimed to determine the difference in activeness using kancing gemerincing model on social studies subjects in class IX of SMPN 11 Malang in the academic year 2019/2020. A quasi-experiment applied in this research with 30 students of grade IX as respondents. The instruments used in this study was test which were consisted of 40 questions and 13 questions on activeness tests. Results showed that the activeness results when implementing kancing gemerincing higher than control class which was implementing PBL models. Results suggest that kancing gemerincing model may be a promising approach to advance student’s activeness involvement in social studies courses. This study offers insight into the prospects for any further research.